Adipose stem cells enhance myoblast proliferation via acetylcholine and extracellular signal–regulated kinase 1/2 signaling. Issue 2 (13th August 2017) - El‐Habta, Roine; Kingham, Paul J.; Backman, Ludvig J.
ABSTRACT: Introduction : In this study we investigated the interaction between adipose tissue–derived stem cells (ASCs) and myoblasts in co‐culture experiments. Methods : Specific inductive media were used to differentiate ASCs in vitro into a Schwann cell–like phenotype (differentiated adipose tissue–derived stem cells, or dASCs) and, subsequently, the expression of acetylcholine (ACh)‐related machinery was determined. In addition, the expression of muscarinic ACh receptors was examined in denervated rat gastrocnemius muscles. Results : In contrast to undifferentiated ASCs, dASCs expressed more choline acetyltransferase and vesicular acetylcholine transporter. When co‐cultured with myoblasts, dASCs enhanced the proliferation rate, as did ACh administration alone. Western blotting and pharmacological inhibitor studies showed that phosphorylated extracellular signal–regulated kinase 1/2 signaling mediated these effects. In addition, denervated muscle showed higher expression of muscarinic ACh receptors than control muscle. Discussion : Our findings suggest that dASCs promote proliferation of myoblasts through paracrine secretion of ACh, which could explain some of their regenerative capacity in vivo . Muscle Nerve 57 : 305–311, 2018